Study on Earnings Management and Corporate Governance: Case of Singapore Stock Exchange - Wasike, Mercy Nasubo (2017)
This study examines earnings management and the nature of its relationship with corporate governance elements. A total of 136 firms over a period of 6 years between 2010 and 2015 were used during the analysis. The research paper applies Modified Jones Model to determine the level of earnings management by measuring discretionary accruals of firms listed in the three main indices found in the Singapore Stock Exchange. Panel data regression analysis was used with the discretionary accruals obtained from the Modified Jones Model as the dependent variable and corporate governance elements as the independent variables, to determine the relationship between corporate governance and earnings management. A total of 8 corporate governance elements were used in the analysis including; board independent members, board size, non-independent members, board meetings, age of CEO, independence of audit committee, CEO duality and ownership of company. The findings showed that there is presence of earnings management in Singapore Stock Exchange. A total of five corporate governance variables were found to significantly affect earnings management. Board size and board meetings both displayed a positive relationship with earnings management while CEO Age, CEO duality and independence of audit committee were found to have a negative relationship with earnings management. The main contribution of the study was incorporating Age of CEO and CEO Duality elements of the board which have not been covered broadly in Singapore. The study concludes by outlining the practical and policy implications of earnings management and its relationship with corporate governance.